Penerapan Metode Permainan Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas 1 SD Negeri 3 Sukajadi - Siva Nurfadila; Dina Rahmawati (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2023)
This PTK is motivated by the low reading ability at the beginning of class I at SDN 3 Sukajadi. This is because the application of the learning method used by the teacher is not quite right, so that students' interest in reading is still lacking and not optimal. The research was conducted because students have not been able to understand the material presented and to improve the learning proces that has not been optimal. This study aims to determine whether the application of the game method can improve the reading ability of the first graders of SDN 3 Sukajadi. The implementation of learning improvement was carried out in two cycles, namely cycle I which was carried out on October 27, 2022, and cycle II which was carried out on November 7, 2022. In the initial learning activities (pre-cycle), it turned out that the initial reading ability of class I students at SDN 3 Sukajadi was still low, namely the value above the KKM is only 33%. After carrying out PTK cycle I, there was an increase in the scores obtained by students above the KKM to 47% and after the implementation of the learning improvement cycle II, the acquisition of student scores increased, namely 100% who got results above the KKM. So it can be concluded that the application of the game method can actually improve the initial reading ability of students I at SDN 3 Sukajadi.